ETHANOLIC DISTILLATION: a case study of ethanol loss upon degassing: DESTILAÇÃO ALCÓOLICA: Um estudo de caso sobre as perdas de etanol na degasagem dos condensadores - Camillo Del Vecchio, Giovanna; Carla Guimarães, Camila; Neves Câmara, Claudionor; Madaleno, Leonardo Lucas (Ciência & Tecnologia, 2024)
Ethanol plays a crucial role in Brazilian and global contexts, serving as a viable and sustainable alternative to fossil fuels. Brazil stands out as a leader in ethanol production, particularly from sugarcane, thereby establishing itself as a benchmark in industrial sustainability. The country’s large-scale production of this biofuel boosts the national economy and promotes diversification of the energy matrix, reducing reliance on nonrenewable fuels. The efficiency of ethanol production is inherently linked to minimizing losses during the process. Therefore, the primary objective of this article was to describe the factors that affect ethanol loss during the degassing process. For this purpose, a case study was conducted involving interviews with operators from the alcohol distillation sector of two sugarcane energy plants and extensive research based on the literature. The findings of this study indicate that parameters such as temperature, pressure, and composition of the wort directly influence ethanol loss during degassing. Furthermore, the alignment between manual and automated activities is an essential factor in overcoming these challenges faced by the sector, ensuring reduced losses in this process and maintaining the quality of the produced ethanol.